2011
DOI: 10.4236/msa.2011.210199
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sn-3.5Ag Alloy Nanosolder by Chemical Reduction Method

Abstract: The synthesis of Sn-3.5Ag alloy nanosolder was investigated by chemical reduction method. In this method, chemical precipitation was achieved by using sodium NaBH<sub>4</sub> as a reducing agent and PVP (poly-m-vinyl 2- pyrrolidone) as a stabilizer. The experimental results obtained with different amounts of NaBH4 and PVP were compared. X-ray diffraction (XRD) patterns revealed that Ag<sub>3</sub>Sn was formed due to the successful alloying process. Scanning Electron Microscopy (SEM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The use of Ag for coating Sn nanoparticles has always been reported at elevated temperature without any reducing agent or at room temperature in the presence of reducing agent or in solvents which possess reducing power, i.e., hexylamine, oleylamine and ethanol. 19,21,[26][27][28][29] The formation of the intermetallic compound between Ag and Sn has been achieved at room temperature without any reducing agent but it was carried out through vacuum evaporation of Sn on Ag thin lm. 23,24 Our observation demonstrated that intermetallic compounds were formed in the organic solvent under the galvanic reduction of the Ag cation by Sn at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The use of Ag for coating Sn nanoparticles has always been reported at elevated temperature without any reducing agent or at room temperature in the presence of reducing agent or in solvents which possess reducing power, i.e., hexylamine, oleylamine and ethanol. 19,21,[26][27][28][29] The formation of the intermetallic compound between Ag and Sn has been achieved at room temperature without any reducing agent but it was carried out through vacuum evaporation of Sn on Ag thin lm. 23,24 Our observation demonstrated that intermetallic compounds were formed in the organic solvent under the galvanic reduction of the Ag cation by Sn at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that PVP acts as a protecting agent of the colloidal particles preventing agglomeration. This has been manifested in different NPs composition like Pd nanoparticles and Sn-3.5Ag alloy NPs [29,38]. However, TEM images in Fig.…”
Section: Electrochemical Characterizationmentioning
confidence: 96%
“…Absorption which looks as a long wavelength tail of intrinsic absorption in a region down to 325 nm is the well-known absorption band of impurity of Fe 3+ [12]. This absorption band near 230 nm has a specific absorption in a soda-lime silicate glass of 3130 cm -1 /W% Fe 3+ [13]. No measurements of the specific absorption of iron were made for the glass but the number above can be used for rough estimations, which gives the total concentration of ferric ions of about 3 ppm.…”
Section: Absorption Spectrum Analysismentioning
confidence: 99%